A Content Management System for Online Shopping Carts - Andarwati, Mardiana; Loo, Petrus; Lazuardi, Dedy; E. , Laxmi Lydia; Rahim, Robbi (International Journal of Psychosocial Rehabilitation, 2020)
A content management system is an application that allows user to produce and modify digital content. A content management system provides a superb many add on inside the design of widgets and plugging to vary and extend its usefulness. Widgets square measure very little applications that user simply just can increase their Internet site to extend its usefulness whereas not having to travel into the code files to form changes. An example of An appliance may be an image carousel that allows user to feature sloppy footage with links to the front page of their Internet site. User may put together install a Google Analytics appliance on content management system dashboard to place their chase code, or terminology widgets to feature text or footage to areas on their page.Plugging or add-ons, add a specific feature to their Internet site. There are literally several getable internet site plugging. Their content management system will go together with some pre-installed ones, e.g. promotional feeds; payment ways, shipping rate computation packages, Face book Connect authentication, and tax suppliers, etc.